2003
DOI: 10.1016/s0886-3350(03)00048-8
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative neodymium:YAG anterior capsulotomy in intumescent cataract: Preventing extension of the capsular tear to the lens periphery

Abstract: Extension of the capsulotomy into the periphery is a well-known complication of cataract surgery in young patients with intumescent cataracts. We report such a case successfully treated preoperatively with a neodymium:YAG laser anterior capsulotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 6 publications
0
14
0
1
Order By: Relevance
“…2 The size, shape, and centration of the capsulorhexis can be variable depending on the type of cataract [3][4][5] as well as the surgeon's experience.…”
mentioning
confidence: 99%
“…2 The size, shape, and centration of the capsulorhexis can be variable depending on the type of cataract [3][4][5] as well as the surgeon's experience.…”
mentioning
confidence: 99%
“…After emulsification of the nucleus, the small CCC was enlarged to the desired diameter. With this technique, CCC was achieved in 57 eyes (95%) (11) ; but other authors reported a 28.3% incidence of incomplete capsulorhexis (12) , within a very low success rate in white cataracts with a liquefied cortex (68%) compared to those with a solid cortex (13) . CCC can also be performed in a sealed anterior chamber (8) using a 27 or 30 gauge needle mounted on a 2.5 ml syringe filled with BSS.…”
Section: Discussionmentioning
confidence: 92%
“…Creating a continuous curvilinear capsulorhexis (CCC) in eyes with white intumescent cataracts is a challenge, because of the difficulty to recognize the intumescent cataract and risk of extension of capsular tears to the lens periphery (2)(3) . Several approaches have been described to avoid this complication (4)(5)(6)(7)(8)(9)(10)(11)(12) , including preoperative neodymium:YAG (Nd:YAG) laser capsulotomy (13) . The objective of this study was to describe the use of preoperative Nd:YAG laser anterior capsulotomy for phacoemulsification in eyes with white intumescent cataracts in terms of the intraoperative difficulties and postoperative outcomes.…”
Section: Introdutionmentioning
confidence: 99%
“…[2][3][4][5][11][12][13][14][15][16][17][18][19][20][21][22][23] The use of trypan blue, 23 puncture of the anterior capsule with positive pressure in the anterior chamber, and 2-stage capsulorhexis 13 have significantly improved the results of senile white cataract surgery. Despite this, the Argentinean flag sign continues to occur.…”
Section: Online Videomentioning
confidence: 99%